Urban Social Assistance : Emerging Insights from Three African Countries - Moreira, Vanessa; Gentilini, Ugo (World Bank, Washington, DC, 2017)
As countries implement social assistance (or safety net) programs, a range of technicalhurdles can affect their implementation differently in rural and urban areas. In urban areas,the focus of this study, cost of living can be higher and more prone to economic slowdowns.Poverty can be more severe than in rural areas and accompanied by high malnutrition rates.Implementation challenges in most urban areas relate to the lack of proper identification,outreach, intake, and registration of potential beneficiaries. These are in part due to thelack of social cohesion and different channels of communication. Therefore, social workersare likely to play an even more fundamental role in program implementation and M&Eprocesses.